2017
DOI: 10.1007/s40071-017-0161-6
|View full text |Cite
|
Sign up to set email alerts
|

Cypermethrin induced stress and changes in growth of freshwater fish Oreochromis niloticus

Abstract: Bioassays were conducted with technical grade and commercial formulation of cypermethrin using freshwater fish Oreochromis niloticus as the test fish. The technical grade cypermethrin contained 92% active ingredient (a.i.) and the commercial formulation was an emulsified concentrate (EC) containing 10% a.i. (10% EC). Based on the actual concentration in water (2 h), the commercial formulation was found to be more acutely toxic to O. niloticus (96-h LC 50 = 4.85 lg/L) than the technical grade cypermethrin (96-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 37 publications
(48 reference statements)
4
11
0
Order By: Relevance
“…In the present study, the results showed that exposure to cypermethrin resulted in a significant decrease in the activities of acid phosphatase and alkaline phosphatase. These results were consistent with the results from similar studies with fish, which also reported a decrease in the activity of both enzymes following exposure to cypermethrin (Majumder & Kaviraj, 2017;Vasantharaja, Pugazhendy, & Meennambal, 2014). The decreased activity of these enzymes may be an indication that cypermethrin elicits its toxic effects in fish through membrane damage F I G U R E 2 Photomicrograph of the small intestine for the control group (a) showing normal histoarchitecture with intact mucosa (m), submucosa (sm), muscle layer (ml), goblet cells (G), villi (red arrows), and intestinal crypts containing intestinal glands (black arrow) surrounded by lamina propria.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the results showed that exposure to cypermethrin resulted in a significant decrease in the activities of acid phosphatase and alkaline phosphatase. These results were consistent with the results from similar studies with fish, which also reported a decrease in the activity of both enzymes following exposure to cypermethrin (Majumder & Kaviraj, 2017;Vasantharaja, Pugazhendy, & Meennambal, 2014). The decreased activity of these enzymes may be an indication that cypermethrin elicits its toxic effects in fish through membrane damage F I G U R E 2 Photomicrograph of the small intestine for the control group (a) showing normal histoarchitecture with intact mucosa (m), submucosa (sm), muscle layer (ml), goblet cells (G), villi (red arrows), and intestinal crypts containing intestinal glands (black arrow) surrounded by lamina propria.…”
Section: Discussionsupporting
confidence: 92%
“…Significant decreases in the RBC, HB, PVC, MCHC, MCH and MCV of toxicant-exposed fish compared to the control in concentration dependent manner could be attributed to anemia. Decline in RBC, MCHC, MCH and MCV suggests stress-induced erythropenia probably caused by hemolysis, inhibition of erythropoiesis and, pathological damage to some tissues and hematopoietic organs as reported by Dogan and Can [8], Akinrotimi et al [36], Majumder and Kaviraj [37] and Özok et al [1]. These are similar to hematological toxicity of endosulfan and phosphamidon on Barbus conchonius [38], diazinon on C. carpio [2], dimethoate on O. mykiss [8] and C. batrachus [35], glyphosate on C. gariepinus [15] and cypermethrin on O. mykiss [2].…”
Section: Discussionmentioning
confidence: 92%
“…However, Velisek et al [2] reported that a higher concentration of 3.4 µg/L of cypermethrin had no effect on the WBC of O. mykiss. Dogan and Can [8] and Ghayyur et al [20] observed reduction in the WBC of O. mykiss and Cirrhinus mrigala exposed to dimethoate, while Majumder and Kaviraj [37] and Amaeze et al [24] observed increase in WBC of Oreochromis niloticus and C. gariepinus exposed to cypermethrin. Narra [35] suggested that in the presence of toxicants, leucopoiesis may increase thus elevating WBC.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to their use in agriculture, pesticides have started to be used in urban and industrial activities, which has led to a continuous increase in pesticide accumulation in aquatic ecosystems (Syafrudin et al, 2021). Rivers, lakes, and ponds are constantly exposed to pesticides through runoff as pesticides dissolve, making fish and aquatic organisms susceptible to the toxic effects of these pesticides (Majumder & Kaviraj, 2022). Cypermethrin is one of the most widely used pesticides worldwide (Ullah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%